Tingkat Pengetahuan Orang Tua Anak Berkebutuhan Khusus (ABK) dalam Pencegahan Cedera Melalui Support Group - Sugiyarto Sugiyarto; Akhmad Rifai (Journal of Telenursing (JOTING), 2021)
This study aims to determine the effect of the support group on the knowledge of parents of children with special needs. The research method uses a quasi-experimental approach with a one-group pretest-posttest approach. Respondents in this study were parents of children with special needs. The number of samples in this study was 50 people. The sampling technique used is consecutive. Data analysis was carried out using the Wilcoxon statistical test because the data were not normally distributed. The results showed that the p-value obtained was 0.001, meaning that there was a significant difference between before and after the support group was carried out regarding the level of knowledge of injury prevention for parents of children with special needs. In conclusion, support groups effectively increase parents' knowledge about preventing injuries to children with special needs. Keywords: Parents of Children with Special Needs, Knowledge of Injury Prevention, Support Group